The 2002 Catholic directory of the Philippines containing status of the Catholic Church in the Philippines as of January 15, 2002. (Catholic Bishops' Conference of the Philippines, 2002)
A directory for the Catholic Church in the Philippines. It provides a hierarchy of the Catholic Church and lists the Catholic institutions by territory and association. It also has indices to parishes and names.